Mystery of bisphenol F-induced nonalcoholic fatty liver disease-like changes: Roles of Drp1-mediated abnormal mitochondrial fission in lipid droplet deposition - Linwei Zhang; Xuexue Xie; Jingxian Tao; Sizhe Wang; Miaoyang Hu; Xi Wang; Zheng Yu; Liuting Xu; Yuxin Lin; Weilan Wu; Jie Cheng; Linlin Wu; et al. (Science of The Total Environment, 2023)

Application of engineered heme enzymes based on myoglobin with high peroxidase activity for efficient degradation of various emerging pollutants - Guang-Rong Wu; Jia-Kun Xu; Li-Juan Sun; Ying-Fu Li; Shu-Qin Gao; Ying-Wu Lin (Journal of Environmental Chemical Engineering, 2023)

Artemisia selengensis Turcz. leaves extract ameliorates hyperuricemia in mice by inhibiting hepatic xanthine oxidase activity, modulating renal uric acid transporters, and improving metabolic disorders - Lin Xiang; Yuting Huang; Rong Li; Yexing Tao; Ting Wu; Siyi Pan; Xiaoyun Xu (Food Bioscience, 2023)

Mitochondria-related lncRNAs: predicting prognosis, tumor microenvironment and treatment response in lung adenocarcinoma - Qianhui Zhou; Jiali Xiong; Yan Gao; Rong Yi; Yuzhu Xu; Quefei Chen; Lin Wang; Ying Chen (Functional & Integrative Genomics, 2023)
Lung cancer is the most common type of malignant tumor that affects people in China and even across the globe, as it exhibits the highest rates of morbidity and mortality. Lung adenocarcinoma (LUAD) is a type of lung cancer with a very high incidence. The purpose of this study was to identify potential biomarkers that could be used to forecast the prognosis and improve the existing therapy options for treating LUAD. Clinical and RNA sequencing data of LUAD patients were retrieved from the TCGA database, while the mitochondria-associated gene sets were acquired from the MITOMAP database. Thereafter, Pearson correlation analysis was carried out to screen mitochondria-associated lncRNAs. Furthermore, univariate Cox and Lasso regression analyses were used for the initial screening of the target lncRNAs for prognostic lncRNAs before they could be incorporated into a multivariate Cox Hazard ratio model. Then, the clinical data, concordance index, Kaplan–Meier (K-M) curves, and the clinically-relevant subjects that were approved by the Characteristic Curves (ROC) were employed for assessing the model's predictive value. Additionally, the differences in immune-related functions and biological pathway enrichment between high- and low-risk LUAD groups were examined. Nomograms were developed to anticipate the OS rates of the patients within 1-, 3-, and 5 years, and the differences in drug sensitivity and immunological checkpoints were compared. In this study, 2175 mitochondria-associated lncRNAs were screened. Univariate, multivariate, and Lasso Cox regression analyses were carried out to select 13 lncRNAs with an independent prognostic significance, and a prognostic model was developed. The OS analysis of the established prognostic prediction model revealed significant variations between the high- and low-risk patients. The AUC-ROC values after 1, 3, and 5 years were seen to be 0.746, 0.692, and 0.726, respectively. The results suggested that the prognostic model riskscore could be used as an independent prognostic factor that differed from the other clinical characteristics. After analyzing the findings of the study, it was noted that both the risk groups showed significant differences in their immune functioning, immunological checkpoint genes, and drug sensitivity. The prognosis of patients with LUAD could be accurately and independently predicted using a risk prediction model that included 13 mitochondria-associated lncRNAs.

Complex coacervation of type II collagen with anionic polysaccharides: Effects of solution pH and molecular conformation of polysaccharide - Rong Xu; Lin Zheng; Sirui Zhang; Mingtao Huang; Mouming Zhao (Food Hydrocolloids, 2023)

Vertical distribution and transport of microplastics in the urban atmosphere: New insights from field observations - Zhen Yuan; Cheng-Lei Pei; Heng-Xiang Li; Lang Lin; Rui Hou; Shan Liu; Kai Zhang; Ming-Gang Cai; Xiang-Rong Xu (Science of The Total Environment, 2023)

Tigliane diterpenoids with cytotoxic activities from Croton damayeshu - Rong-Lin Jia; Qian Liang; Jia-Xin Hu; Si-Da Xie; Xiao-Min Su; Wen-Hui Xu (Phytochemistry Letters, 2023)

Regulation on copper-tolerance in Citrus sinensis seedlings by boron addition: Insights from root exudates, related metabolism, and gene expression - Huan-Huan Chen; Zhi-Chao Zheng; Wen-Shu Chen; Rong-Yu Rao; Xu-Feng Chen; Xin Ye; Jiuxin Guo; Lin-Tong Yang; Li-Song Chen (Journal of Hazardous Materials, 2023)

Neurobehavioral disorders induced by environmental zinc in female zebrafish (Danio rerio): Insights from brain and intestine transcriptional and metabolic signatures - Fan Yu; Zhi-Shuai Hou; Hong-Rui Luo; Hong-Xia Li; Xue-Fan Cui; Jian-Lin Li; Wen-Rong Feng; Yong-Kai Tang; Sheng-Yan Su; Qin-Feng Gao; Jun Xiao; Pao Xu (Chemosphere, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

The occurrence of "yellowing" phenomenon and its main driving factors after the remediation of chromium (Cr)-contaminated soils: A literature review - Hao-Kai Li; Da-Mao Xu; Jun-Xian Wang; Ze-Lin Xu; Rong-Bing Fu (Journal of Hazardous Materials, 2023)

Clinical poisoning events involving yunaconitine may be highly correlated with metabolism-based interactions: A critical role of CYP3A4 - Xiaocui Li; Yu Fu; Huawei Qiu; Xueyu Xu; Tingting Lin; Weiqing Hou; Weiying Chen; Rong Zhang; Zhongqiu Liu; Lijun Zhu (Food and Chemical Toxicology, 2023)

High-resolution forest age mapping based on forest height maps derived from GEDI and ICESat-2 space-borne lidar data - Xudong Lin; Rong Shang; Jing M. Chen; Guoshuai Zhao; Xiaoping Zhang; Yiping Huang; Guirui Yu; Nianpeng He; Li Xu; Wenzhe Jiao (Agricultural and Forest Meteorology, 2023)

A study of the lipid profile of Coix seeds from four areas based on untargeted lipidomics combined with multivariate algorithms to enable tracing of their origin - Peng Chen; Yabo Shi; Xiaoyan Xiao; Rong Xue; Yu Li; Lin Li; Chunqin Mao; Tulin Lu; Conglong Xu (Food Research International, 2023)

SHP2: its association and roles in systemic lupus erythematosus - Chan Yang; Rong Li; Lin-Chong Su; You-Yu Lan; You-Qiang Wang; Wang-Dong Xu; An-Fang Huang (Inflammation Research, 2023)

Mechanistic insights into the migration behavior of cadmium (Cd) in the soil and groundwater systems at a construction site: Experimental and numerical analysis - Da–Mao Xu; Ze–Lin Xu; Zi–Qi Mu; Bai–Hong An; Xiao–Wen Fang; Rong–Bing Fu (Journal of Environmental Chemical Engineering, 2023)

An effective tool for tracking steroids and their metabolites at the watershed level: Combining fugacity modeling and a chemical indicator - Ru Xu; Shan Liu; Hui Chen; Qin-Wei Hao; Yong-Xia Hu; Heng-Xiang Li; Lang Lin; Rui Hou; Bing Hong; Shen Yu; Xiang-Rong Xu (Environmental Pollution, 2023)

Free and conjugated forms of metabolites are indispensable components of steroids: The first evidence from an estuarine food web - Shan Liu; Ru Xu; Yun-Feng Pan; Qian-Yi Huang; Nian-Nian Wu; Heng-Xiang Li; Lang Lin; Rui Hou; Xiang-Rong Xu (Water Research, 2023)

Quantum neuronal sensing of quantum many-body states on a 61-qubit programmable superconducting processor - Ming Gong; He-Liang Huang; Shiyu Wang; Chu Guo; Shaowei Li; Yulin Wu; Qingling Zhu; Youwei Zhao; Shaojun Guo; Haoran Qian; Yangsen Ye; Chen Zha; et al. (Science Bulletin, 2023)

QTL-seq and transcriptomic integrative analyses reveal two positively regulated genes that control the low-temperature germination ability of MTP–maize introgression lines - Ru-Yu He; Jun-Jun Zheng; Yu Chen; Ze-Yang Pan; Tao Yang; Yang Zhou; Xiao-Feng Li; Xinyi Nan; Ying-Zheng Li; Ming-Jun Cheng; Yan Li; Yang Li; et al. (Theoretical and Applied Genetics, 2023)

A systematic analysis and evaluation of nutritional composition of 23 strains of marine microalgae commonly used in aquaculture - Jia-Xing Zhang; Zhao-Shou Ran; Hai-Xuan Xie; Fei Kong; Meng-Qi Zhang; Yao Zhou; Yan-Rong Li; Kai Liao; Xiao-Jun Yan; Ji-Lin Xu (Algal Research, 2023)

Adsorption of heavy metals on biodegradable and conventional microplastics in the Pearl River Estuary, China - Min Shi; Qun Xie; Zhen-Liang Li; Yun-Feng Pan; Zhen Yuan; Lang Lin; Xiang-Rong Xu; Heng-Xiang Li (Environmental Pollution, 2023)

Interaction Between the Glymphatic System and α-Synuclein in Parkinson’s Disease - Yu Zhang; Cui Zhang; Xu-Zhong He; Zhen-Hua Li; Jing-Cai Meng; Rui-Ting Mao; Xin Li; Rong Xue; Qian Gui; Guo-Xing Zhang; Lin-Hui Wang (Molecular Neurobiology, 2023)

Activating α7nAChR helps post-myocardial infarction healing by regulating macrophage polarization via the STAT3 signaling pathway - Xiao-Hui Niu; Rong-Hua Liu; Xiao Lv; Rui-Lin He; Fang-Zhou Lv; Shu-Jie Wu; Xu-Qing Li; Lei Li; Jia-Feng Lin (Inflammation Research, 2023)

Whole-genome sequencing reveals putative underlying mechanisms of biocontrol capability of IBFCBF-5 - Chen Luo; Ai-rong Shen; Ye-song Ren; Yang Zhai; Yi Cheng; Jianping Xu; Lin Wei; Ji-lie Li; Liang-bin Zeng (Acta Physiologiae Plantarum, 2023)

Geochemical record of methane seepage in carbon cycling and possible correlation with climate events in the Qiongdongnan basin, South China Sea - Xiaopeng Dan; Shuang Liu; Xiuli Feng; Lin Lin; Rong Tang; Chao Yang; Jinya Xu; Zihan Wu (Marine and Petroleum Geology, 2023)

Shaking table tests and seismic assessment of a full-scale precast concrete sandwich wall panel structure with bolt connections - Jia-Xuan He; Zhao-Dong Xu; Lian-Yu Zhang; Zhi-Hua Lin; Zhong-Wei Hu; Qiang-Qiang Li; Yao-Rong Dong (Engineering Structures, 2023)

Risk assessment and environmental determinants of urinary phthalate metabolites in pregnant women in Southwest China - Nian Wu; Lin Tao; Kunming Tian; Xia Wang; Caidie He; Songlin An; Yingkuan Tian; Xiang Liu; Wei Chen; Haonan Zhang; Pei Xu; Dengqing Liao; et al. (Environmental Science and Pollution Research, 2023)

Expanded polystyrene buoys as an important source of hexabromocyclododecanes for aquatic ecosystem: Evidence from field exposure with different substrates - Yun-Feng Pan; Shan Liu; Heng-Xiang Li; Lang Lin; Rui Hou; Yuan-Yue Cheng; Xiang-Rong Xu (Environmental Pollution, 2023)

Short-Term Limited Water Irrigation Influences the Photosynthetic Pigments, Enzymatic and Non-Enzymatic Activities in Saccharum spontaneum L. at Vegetative Stage - Zhi-Nian Deng; Hai-Rong Huang; Cheng-Mei Huang; Krishan K. Verma; Hai-Bin Luo; Sheng-Li Jiang; Yi-Jie Li; Hui-Qing Cao; Kai-Chao Wu; Lin Xu (Sugar Tech, 2023)

Concentrations, congener patterns, and correlations of unintentional persistent organic pollutants in cement kilns co-processing hazardous waste - Changzhi Chen; Haoyang Wang; Guorui Liu; Bingcheng Lin; Lili Yang; Rong Jin; Yuxiang Sun; Jianping Guo; Yinming Li; Nan Yang; Aihong Li; Changliang Li; et al. (Science of The Total Environment, 2023)

Boosting persulfate activation via paper mill sludge-based biochar for efficient degradation of bisphenol A: Inherent multiple active sites - Zhi-Juan Wang; Yang-Qian Lin; Hua-Jing Zhou; Zi-Lian Liu; Rong-Rong Miao; Xi-Meng Xu; Liang He; Qing-Qing Guan (Chemical Engineering Journal, 2023)

Sn2P2S6: A lead-free reversible thermochromic ferroelectric with high near-infrared reflectance - Meixia Wu; Xiao Zhou; Xihui Liang; Yifeng Han; Yonghong Li; Xingan Jiang; Xueyun Wang; Yisheng Chai; Xiang Zhou; Hui Yang; Dan Lin; Ping Xu; et al. (Chemical Engineering Journal, 2023)